2020
DOI: 10.1007/s00787-020-01471-1
|View full text |Cite
|
Sign up to set email alerts
|

Autism spectrum disorder and attention-deficit/hyperactivity disorder in children with cerebral palsy: results from screening in a population-based group

Abstract: Autism spectrum disorder (ASD) and attention-deficit/hyperactivity disorder (ADHD) are more common in children with cerebral palsy (CP) than in the general population, but may still be underdiagnosed. This study aimed to estimate screen-positive ASD and ADHD in a population-based group of 264 school-aged children with CP born 1999–2006 from the CP register of western Sweden. Validated parent-completed questionnaires were used at a median age of 12 years 11 months (range 8–17 years). Three different scales were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…There is a need to adjust the cut‐offs to be more accurate regarding ADHD. Screening tools with fewer items than in our original questionnaire are also needed 7,13 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There is a need to adjust the cut‐offs to be more accurate regarding ADHD. Screening tools with fewer items than in our original questionnaire are also needed 7,13 …”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported attention deficits but not diagnoses, while some have used a screening procedure for ADHD symptoms rather than diagnoses. 7,13 By interviewing parents, Bjorgaas et al 4 identified symptoms of ADHD in 50% of children in GMFCS levels I to IV. Studies based on records and registers most likely underestimate the prevalence of autism and ADHD and screening usually includes more children than those actually meeting the diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations